The influence of globalization and information technologies on international law - Qahramonova Aziza Ulugʻbek qizi (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
In this article, globalization and information technologies are considered as one of the main reasons which impacted on international law. The author highlights how globalization and information technology have profoundly impacted on international law in different ways. The article also comprehensively analyzes in which ways IT and globalization have an effect on international and the opinions of specialists in this sphere have been studied.